Barbara J. Bachmann; Henry Branch Howe, Jr. - Ray Barratt; Sara Neville Bennett (Fungal Genetics Reports, 1999)
Obituaries for Barbara J. Bachmann, Ph.D. 1924-1999, and Henry Branch Howe, Jr. Ph D. 1924-1998.